2013
DOI: 10.1186/cc12824
|View full text |Cite
|
Sign up to set email alerts
|

Five-year risk of end-stage renal disease among intensive care patients surviving dialysis-requiring acute kidney injury: a nationwide cohort study

Abstract: IntroductionDialysis-requiring acute kidney injury (D-AKI) is common among intensive care unit (ICU) patients. However, follow-up data on the risk of end-stage renal disease (ESRD) among these patients remain sparse. We assessed the short-term and long-term risk of ESRD after D-AKI, compared it with the risk in other ICU patients, and examined the risk within subgroups of ICU patients.MethodsWe used population-based medical registries to identify all adult patients admitted to an ICU in Denmark from 2005 throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 30 publications
0
57
1
1
Order By: Relevance
“…The 5-year risk of ESRD in these patients was 3.8% compared with 0.3% in patients who did not require dialysis. 22 Even though the setting was different in the Danish study, the risk of ESRD was similar to that in our cohort. In the Danish study, the association between AKI and ESRD was stronger in patients with normal kidney function than in those with chronic kidney disease.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…The 5-year risk of ESRD in these patients was 3.8% compared with 0.3% in patients who did not require dialysis. 22 Even though the setting was different in the Danish study, the risk of ESRD was similar to that in our cohort. In the Danish study, the association between AKI and ESRD was stronger in patients with normal kidney function than in those with chronic kidney disease.…”
mentioning
confidence: 80%
“…Several previous epidemiological studies in various clinical settings reported an association between AKI and ESRD. 10,11,[22][23][24] AKI requiring dialysis in the immediate postoperative period is an independent risk factor for mortality. 5 Even though only ≈0.6% of patients need dialysis during the postoperative period, this is an important prognostic factor for both all-cause mortality and long-term dialysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…57 It is now known that AKI acquired in the ICU has important long-term sequelae, including an increased risk for ESRD. 58 However, both the number of patients and the duration of follow-up required to address end points, such as ESRD, make it unlikely that pharmacologic interventional trials with sufficient statistical power to show effects on these long-term consequences of ICUacquired AKI will be conducted in the near future. Therefore, the primary aim of clinical research in AKI should be to determine whether a new intervention actually ameliorates inflammationassociated kidney tissue damage during the patient's clinical stay.…”
Section: Study Design Considerations and Challenges For Clinical Triamentioning
confidence: 99%
“…18 Worsening AKI was defined as an increase in RIFLE category (from RISK to INJURY, RISK to FAILURE, or INJURY to FAILURE) in the 48 hours after enrollment or renal replacement therapy (RRT) initiation, as previously defined. 19 Baseline serum creatinine was defined as the lowest creatinine value in the last 6 months before AKI or, for those without this measurement, the lowest value achieved during hospitalization in the absence of dialysis. 20 Day 0 was defined as the calendar day of admission and thus its length varied depending on the time of presentation.…”
Section: Methodsmentioning
confidence: 99%